Emergencies Under Czech Law - Zdenek Kühn (European Journal of Risk Regulation)
The paper outlines Czech constitutional law and the development of emergency law. Initially, the legislature did not expect emergencies to occur, perhaps due to the idealistic optimism associated with the general atmosphere of the collapse of the Eastern Bloc in 1989 and the “End of History” thesis. As a result, emergencies were not regulated by Czech law in the 1990s. This changed after the great floods at the end of the 1990s, when “history returned,” and the need for some special rules for emergencies became clear. The first decades of this century showed that Czech emergency law worked well for short-term natural disasters. The game-changer came in 2020, with the emergence of the COVID-19 pandemic and the need for a long-term state of emergency. It soon became clear that the rules that worked for floods and other disasters did not work for long-term global pandemics. In other words, the legal system was not prepared for a situation in which emergencies were the rule rather than the exception. Legislators were unable to prepare a long-term legislative response to fill this gap. The memory of COVID-19 is fading fast, and there are no plans to reform the relevant legislation. Accordingly, any new pandemic or similar event will lead to the same problems that the Czech legal system had to deal with from 2020 to 2022.